2003
DOI: 10.4028/www.scientific.net/ssp.94.45
|View full text |Cite
|
Sign up to set email alerts
|

The Strain Induced Cementite Dissolution in Carbon Steel - Experimental Facts and Theoretical Approach

Abstract: The evolution of microstructure and phase composition of the carbon steel UIC 860 during high pressure torsion in the wide strain range g = 62 -300 was investigated. Complete cementite dissolution was observed in steel after deformation g = 300. It is suggested that the decrease of thermodynamic stability of the carbides is connected with the high stress levels inside the cementite particles caused by shear stresses at their surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Moreover, a WEL has been produced for much lower slip levels, which justifies predominantly mechanically-induced WEL formation assisted by temperature. Indeed, a moderate increase of temperature could catalyze the kinetics of cementite dissolution [23,72]. Thus, it can be unambiguously stated that temperature is rather secondary in the formation of the WELs reproduced in this study.…”
Section: Effect Of the Sliding Ratiosupporting
confidence: 71%
“…Moreover, a WEL has been produced for much lower slip levels, which justifies predominantly mechanically-induced WEL formation assisted by temperature. Indeed, a moderate increase of temperature could catalyze the kinetics of cementite dissolution [23,72]. Thus, it can be unambiguously stated that temperature is rather secondary in the formation of the WELs reproduced in this study.…”
Section: Effect Of the Sliding Ratiosupporting
confidence: 71%
“…For example, experiments were conducted on an extra-fine nickel powder produced by ball milling (BM) and having a nanocrystalline structure with a mean particle size of ~20 nm [23]. Powders of a nanocrystalline Fe-1%C alloy produced by mechanical alloying were consolidated to form a bulk nanocrystalline sample by HPT, and the density of the compacts was ~96% of the theoretical density [24]. Powders of a nanocrystalline Fe-1%C alloy produced by mechanical alloying were consolidated to form a bulk nanocrystalline sample by HPT, and the density of the compacts was ~96% of the theoretical density [24].…”
Section: Using Hpt For the Cold Consolidation Of Powders And Machininmentioning
confidence: 99%
“…One of these is based on thermodynamic equilibrium considerations in metastable phases; [155,156] the other is based on ballistic models in which movement of matter is caused by external factors. [159] For small precipitates, the relaxation of interface energy and interface stresses provides a high driving force for their dissolution, because dissolution of precipitates leads to relaxation of these strain fields. This is caused by 4: Solid State Processing, Fecht and Ivanisenko 153 two factors: their very small size, so that capillarity effects become important, [45,158] and accumulation of strains in the precipitates.…”
Section: Dissolution Of Precipitatesmentioning
confidence: 99%
“…The grain size in the resulting compacts is strictly dependent on the grain and particle size of the initial powders, and also on the consolidation conditions. [167] TEM investigations had shown that the microstructure of the compacts consists of nanocrystalline ferritic matrix with grain size of 70 nm and fine carbide and oxide particles distributed basically along the grain boundaries ( Fig. [164] HPT processing of powder blends of metal and metal oxides results in formation of nanocomposites consisting of nanocrystalline matrix (d ∼ 50-70 nm) and embedded oxide particles.…”
Section: Consolidation Of Powders and Synthesis Of Nanocompositesmentioning
confidence: 99%